Henry and Mudge under the yellow moon : the fourth book of their adventures - Rylant, Cynthia; e (New York : Bradbury Press, 2003)
In the autumn Henry and his big dog Mudge watch the leaves turn, meet with some Halloween spooks, and share Thanksgiving dinner.
G2
Keywords: Dogs -- Fiction; Autumn -- Fiction